Adding Haystacks to Our Needles? Assessing Changes in Collection Composition after the Introduction of Uncurated Packages. Issue 1 (2nd January 2019) - Jabaily, Matthew J.; Glazier, Rhonda; Gates, Lynn E.
Abstract: Although academic library print collections are traditionally carefully selected, collection strategies for online materials often involve the addition of large, uncurated packages of eBooks and other online materials. This study examines how adding such packages has altered the composition of one library's collection in terms of publication date, format, and subject. It then utilizes WebPAC and Summon search results to understand how the collection is experienced by library searchers. Results show rapid growth in uncurated collections. Whereas WebPAC heavily favored newer items and eBooks from uncurated collections, Summon promoted print books from cultivated collections to a degree greater than expected.